ENCRYPTION AND DATA PROTECTION TECHNOLOGIES AND EVALUATION OF THE EFFECTIVENESS OF ALGORITHMS (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: This paper explores the critical role of encryption and data protection technologies in securing sensitive information in modern digital environments. It investigates the various encryption methods, their applications, and the latest advancements in data protection techniques. The study also focuses on evaluating the effectiveness of algorithms used for securing data, analyzing factors such as performance, reliability, and robustness against potential cyber threats. By examining both symmetric and asymmetric encryption algorithms, the paper highlights their strengths, weaknesses, and suitability for different use cases. The evaluation framework provided in this work aims to offer insights into optimizing data protection strategies in an increasingly complex digital landscape.